1986
DOI: 10.1111/j.1095-8649.1986.tb04966.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between feeding preferences and consumption rates in grass carp and grass carp × bighead carp hybrids

Abstract: The relationship between food preference hierarchy and consumption rate was examined for the grass carp, Cfrnopharygodon idella, and its F1 hybrid (grass carp x bighead carp). Preferences of both types of fish were similar, although hybrids consumed vegetation at a much lower rate. For both, relative preference in feeding trials with mixed plant species was significantly correlated with consumption rate in monospecific feeding experiments. N o correlations were found between preference and caloric content, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
1
17
0
1
Order By: Relevance
“…Fato contrário foi verificado para Ceratophyllum demersum, em que ocorreu redução significativa da eficiência de seu controle quando colocada juntamente com uma das espécies de Egeria, no experimento 1 com período de duração de três dias (Tabela 4), concordando com Duthu & Kilgen (1975), Wiley et al (1986) Segundo Wiley et al (1986), os peixes preferem as plantas que podem consumir mais rapidamente, otimizando o ganho de energia, uma vez que esses mesmos autores verificaram que não existe correlação entre a preferência de consumo da carpa-capim e o conteúdo de proteína e energia das plantas daninhas aquá-ticas.…”
Section: Resultsunclassified
“…Fato contrário foi verificado para Ceratophyllum demersum, em que ocorreu redução significativa da eficiência de seu controle quando colocada juntamente com uma das espécies de Egeria, no experimento 1 com período de duração de três dias (Tabela 4), concordando com Duthu & Kilgen (1975), Wiley et al (1986) Segundo Wiley et al (1986), os peixes preferem as plantas que podem consumir mais rapidamente, otimizando o ganho de energia, uma vez que esses mesmos autores verificaram que não existe correlação entre a preferência de consumo da carpa-capim e o conteúdo de proteína e energia das plantas daninhas aquá-ticas.…”
Section: Resultsunclassified
“…data). The order of macrophyte selection observed was similar to that reported for grass carp ( Ctenopharyngodon idella ) by Wiley, et al (), with the exception of V. americana , which was not included in their study. Preferential selection of N. flexilis by rudd was consistent with the selection of Najas guadalupensis by grass carp in a southern US reservoir (McKnight & Hepp ), but contrary to the avoidance of N. flexilis by age‐0 grass carp in an experimental pond in Florida (Colle et al .,).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the macrophyte species in our study did not differ statistically in mean %N or concentration of proteins, and the range of means was rather narrow among species. Departures from selection of the most nutritious macrophytes available have been reported for the crayfish Orconectes virilis (Chambers, Hanson & Prepas, ) and Procambarus clarkii (Cronin et al ., ), the pond snail ( L. stagnalis ; Elger & Lemoine, ), grass carp (Wiley et al ., ; Pine & Anderson, ), common carp (Miller & Provenza, ) and Canada goose ( Branta canadensis ; Buchsbaum et al ., ). The nutritional value of macrophytes is often considered in terms of protein and N content because herbivores are assumed to be N‐limited; however, this approach overlooks the potential importance of micronutrients for the formation of bones and shells in herbivores (Bonar et al ., ; La Pierre et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…@ Total crayfish biomass (wet, g) C. hispida C. submersum Selective grazing on living macrophytes has been previously observed in other aquatic animals such as fishes (Prejs 1984, Wiley et al 1986), snails (Sheldon 1987, Brbnmark 1989, insects (Cronin et al 1999, Dorn et al 2001) and other crayfish species (Seroll and Coler 1975, Chambers et al 1991, Lodge 1991, Matthews et al 1993. Nevertheless, in most cases, the biotic and abiotic factors responsible for the observed selective grazing were unclear.…”
Section: Smallmentioning
confidence: 93%
“…Nevertheless, in most cases, the biotic and abiotic factors responsible for the observed selective grazing were unclear. Lodge (1991), after reviewing and evaluating data fiom several of these works (Seroll and Coler 1975, Prejs 1984, Wiley et al 1986, Sheldon 1987, BrSnrnark 1989, found that concentrations of protein, cellulose, and lignin in tissues of preferred and unpreferred macrophytes did not differ significantly among preference categories. Lodge (1991) also found that phenolic content, but not alkaloid content, in tissues of preferred and unpreferred rnacrophytes was negatively related to the grazing preference of Orconectes rurticur (crayfish), Physa gyrina (snail), and Ctenophcnyngodon idella (fish), suggesting that phenolic compounds can negatively affect macrophyte choice by a diversity of aquatic grazers.…”
Section: Smallmentioning
confidence: 97%